Commonly used chemicals in shrimp ghers at Shyamnagar upazila in Satkhira, Bangladesh (Research in Agriculture Livestock and Fisheries, 2015)
The study was carried out to know the purpose of the use of chemicals and current status of chemicals used in various aquaculture activities in Shyamnagar upazila between August 2007 and February 2008. A total of 50 shrimp farmers and chemical sellers were selected for questionnaire interview. Data were collected through PRA tools like questionnaire interview, Focus Group Discussion and key informant interview. All interviewed farmers were male with an average age of 36-45 years and their average family size was 7 members. Commonly used chemicals found in the study area were lime, urea, Triple super phosphate (TSP), Potassium permanganate, Vitamins, Antibiotics, (mainly oxytetracycline and chlorotetreacycline), rotenone, phosphate, phostoxin, sumithion, melathion, timsen, bioaqua, oxymax/oxyflow, aquanarish, aqua clean and théoden. Health management and disease treatment were the major activities where farmers were seen to use a lot of chemicals. Study identified some diseases and conditions like white spot disease, yellow head disease, heavy gill and surface fouling disease, brown spot disease, nutritional disease and environmental disease. This study demonstrated that most of the farmers used chemicals and antibiotics indiscriminately without knowing their mode of action, doses and appropriate procedure of application. Study also shows that farmer used various types of chemicals but did not get benefit only little exception due to shrimp viral disease. The study also highlighted the names and approximate price of aquaculture chemicals available with the chemical sellers in the study areas.Res. Agric., Livest. Fish.2(2): 343-351, August 2015